Evaluating the internal control system for managing PBB-P2 receivables in Majene Regency, West Sulawesi Province - Arianto Arianto; Nanda Ayu Wijayanti (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study aimed to evaluate the effectiveness and examine the efforts made to overcome potential internal control system constraints in managing PBB-P2 Receivables in Majene Regency. Research methodology: Data collected through interviews and questionnaire distribution were analyzed using qualitative descriptive analysis to assess the effectiveness of SPI. The analysis also evaluated the constraints and efforts made to overcome SPI’s weaknesses of SPI in managing PBB-P2 Receivables in Majene Regency. Results: The results showed that the internal control system of BAPENDA Majene Regency was not effective in managing PBB-P2 Receivables because of weaknesses in the control and monitoring of environment elements. The implementation of internal controls is hindered by low taxpayer compliance due to inadequate information regarding PBB-P2 Receivables. Another obstacle is the inaccurate calculation of receivables, because it is not supported by clear details. In addition, internal control is hindered by the absence of an up-to-date NJOP. Limitations: This study was limited to the value of PBB-P2 Receivables for Majene Regency during 2016-2020. Contribution: The results are expected to provide additional information regarding the factors influencing the management of PBB-P2 Receivable collection. The findings also provide advice and evaluation for regional governments, especially the Regional Revenue Agency of Majene Regency.